Apolinario Mabini: Paghamon sa Tadhana ng Mapanghimagsik na Kamalayan (APOLINARIO MABINI: CHALLENGING FATE BY REVOLUTIONARY INTELLIGENCE) - San Juan, Epifanio (Social Sciences and Development Review, 2017)
The thought and practice of Apolinario Mabini laid the theoretical foundation of the Filipino revolutionary movement inspired by Rizal and Bonifacio’s Katipunan. While educated by the colonial educational system, Mabini drew inspiration from his peasant roots and his immersion in the revolutionary struggles of the Katipunan and the peasant-worker army of the revolutionary government headed by General Aguinaldo. Based on his synoptic critique of his experiences as prime minister of the first Philippine Republic, Mabini discerned the need for both inner/psychic transformation and external/sociopolitical change around him. He laid the foundation for an indigenous materialist dialectic of freedom and international solidarity. His articulation of the growth of historical consciousness among the masses—from the martyrdom of the priests Burgos, Gomez and Zamora, to Rizal’s writings, and Bonifacio’s organizational wisdom, Mabini formulated the need for democratic principles and moral rectitude in guiding the collective praxis of national-popular energies toward full sovereignty and progressive ideals. His distinguished contribution to our cultural heritage remains a challenging imperative for all citizens desiring genuine freedom as a people with proven dignity and an integral tradition of indigenous, innovative creativity.
Keywords: contradiction; revolution; mass; dialectics; reason; freedom